2023
DOI: 10.1002/csc2.20874
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of potato glycoalkaloids and its potential to control severity of dry rot caused by Fusarium sulphureum

Abstract: Identifying novel sources of antifungal agents from common food waste (i.e., green potato peel) could provide an inexpensive alternative for botanical fungicides. Identification of the potato (Solanum tuberosum L.) glycoalkaloids (PGAs) content in the green peel by high performance liquid chromatography (HPLC), and the antifungal activity of PGAs against the potato dry rot pathogen Fusarium sulphureum were evaluated using addition of PGAs to the medium in vitro and injection of it into potato tubers in vivo. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…PGA could inhibit the colony growth of pathogenic fungi such as A. solani ( Wolters et al, 2023 ) and P. brasiliense ( Joshi et al, 2021 ). PGA inhibited the mycelial growth rate and spore germination of C. trifolii ( Xu et al, 2023 ), and inhibited the growth of F. sulphureum by inhibiting ROS metabolism and destroying cell membrane ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGA could inhibit the colony growth of pathogenic fungi such as A. solani ( Wolters et al, 2023 ) and P. brasiliense ( Joshi et al, 2021 ). PGA inhibited the mycelial growth rate and spore germination of C. trifolii ( Xu et al, 2023 ), and inhibited the growth of F. sulphureum by inhibiting ROS metabolism and destroying cell membrane ( Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PGA can inhibit the growth and development of Botrytis cinerea ( Sun et al, 2014 ), Pectobacterium carotovorum ( Rocha et al, 2015 ), Alternaria alternata and Pyrenophora tritici-repentis ( Sanchez-Maldonado et al, 2016 ), Phytophthora infestans ( Dahlin et al, 2017 ). PGA could inhibit the spore germination of Curvularia trifolii ( Xu et al, 2023 ), reduce the virulence of Pectobacterium brasiliense ( Joshi et al, 2021 ), inhibit the active oxygen metabolism process of F. sulphureum to exert antifungal effect ( Li et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The foliar total glycoalkaloids (TGA) level in potatoes is highly associated with resistance against pests, such as the Colorado potato beetle (Leptinotarsa decemlineata) and the potato leafhopper (Empoasca fabae) (Sinden et al 1980;Tingey 1984;Sanford et al 1992;Friedman et al 1997). It has also been shown that α-chaconine can inhibit the growth of several fungi and nematodes (Fewell & Roddick 1993;Li et al 2022).…”
Section: Role In Plant Resistancementioning
confidence: 99%
“…spermidine) and osmoregulatory hexoses (Castro-Moretti et al, 2020). Elevated levels of glycoalkaloids (toxic to humans) are produced in potato tubers trying to resist root rot pathogens like Fusarium sulphureum (Li et al, 2022). In a wonderful example of a soil microbiome preserving a healthy plant metabolome, maize was grown on sterile sand inoculated with soil bacteria that had been filter purified of all protists (predators of bacteria), while some plants were also inoculated with a blend of these bacterial predators: the ciliate (Tetrahymena pyriformis), an amoebae (Acanthamoeba polyphaga) and a flagellate (Cercomonas longicauda).…”
Section: Mitigating Root Stress By Modifying the Rhizospherementioning
confidence: 99%